Sinapicacid Inhibits Group IIA Secretory Phospholipase A2 and Its Inflammatory Response in Mice - Aladahalli S. Giresha; Deepadarshan Urs; Sophiya Pundalik; Rajkumar S. Meti; Siddanakoppalu N. Pramod; Ballenahalli H. Supreetha; Madhusudana Somegowda; Kattepura K. Dharmappa; Ahmed M. El-Shehawi; Sarah Albogami; Mona M. Elseehy; Abdullah Alaklabi; et al. (Antioxidants, 2022)
Human Group IIA secreted phospholipase A2 (sPLA2-IIA) enzyme plays a crucial role in several chronic inflammatory diseases such asasthma, atherosclerosis, gout, bronchitis, etc. Several studies showed that the antioxidants exert an anti-inflammatory function by inhibiting the sPLA2-IIA enzyme. Hence, the present study evaluated an antioxidant molecule, sinapic acid, for sPLA2-IIA inhibition as an anti-inflammatory function. Initially, the antioxidant efficacy of sinapic acid was evaluated, and it showed greater antioxidant potency. Further, sinapic acid inhibited 94.4 ± 4.83% of sPLA2-IIA activity with an IC50 value of 4.16 ± 0.13 µM. The mode of sPLA2-IIA inhibition was examined by increasing the substrate concentration from 30 to 120nM and the calcium concentration from 2.5 to 15 mM, which did not change the level of inhibition. Further, sinapic acid altered the intrinsic fluorescence and distorted the far UltraViolet Circular Dichroism (UV-CD) spectra of the sPLA2-IIA, indicating the direct enzyme-inhibitor interaction. Sinapic acid reduced the sPLA2-IIA mediated hemolytic activity from 94 ± 2.19% to 12.35 ± 2.57% and mouse paw edema from 171.75 ± 2.2% to 114.8 ± 1.98%, demonstrating the anti-inflammatory efficiency of sinapic acid by in situ and in vivo methods, respectively. Finally, sinapic acid reduced the hemorrhagic effect of Vipera russelli venom hemorrhagic complex-I (VR-HC-I) as an anti-hemorrhagic function. Thus, the above experimental results revealed the sinapic acid potency to be an antioxidant, anti-inflammatory and anti-hemorrhagic molecule, and therefore, it appears to be a promising therapeutic agent.